Efeito de Produtos Fitossanitários Naturais Sobre Beauveria bassiana (Bals.) Vuill. in vitro - Mertz, Natalia Ramos; Alves, Luís Angeli; Marcomini, Angelina; de Oliveira, Daian Pinto; dos Santos, Juliana (BioAssay, 2010)
The associated use of natural products with entomopathogenic fungi can be an efficient strategy to pest and disease control and to reduce the environmental impacts, however, these products can act adversely against the fungi, affecting its vegetative growth, conidiogenesis, viability and pathogenicity. In view of the above, were evaluated the in vitro effects of the commercial products Agro-mos®, Ecolife® and Dalneem® (concentrations 0.25; 0.5; 1; 2 and 4%) and the plant extracts of Curcuma longa (Zingiberaceae), Cymbopogon citratus and Cymbopogon nardus (Poaceae) (1; 5; 10; 15 e 20%) against Beauveria bassiana, which were mixed in a Potato Dextrose Agar (PDA) medium, into Petri dishes. Were verified the micelial growth, the conidiogenesis and the conidia viability, besides the fungi pathogenicity, when produced in contact with these products, against Galleria mellonella (Lepidoptera: Pyralidae) caterpillars. The commercial products affected all the parameters, being toxic in all concentrations and the plant extracts reduced the viability in at least 50% when compared to the control. Curcuma longa was compatible to fungi in the 1% concentration, Cymbopogon citratus was compatible until 15% and Cymbopogon nardus until 10% and all of them did not affect the fungi virulency. The results prove the necessity of such studies in order to do not affect the action of biological control agents.